1981
DOI: 10.3168/jds.s0022-0302(81)82745-2
|View full text |Cite
|
Sign up to set email alerts
|

Milk Yield, Feed Intake, Prolactin, Growth Hormone, and Glucocorticoid Response of Cows to Supplemented Light

Abstract: Milk production and dry matter intake of 21 cows subjected to 16 h of fluorescent light and 8 h dark and of 21 cows subjected to natural light 9 to 12 h daily between October 25 and March 14 were measured beginning in early (37 to 74 days postpartum) and late (94 to 204 days postpartum) lactation. Cows that received 16 h of fluorescent light produced 6.7% (1.4 kg) more milk per day (adjusted for parity and pretreatment production) than cows exposed to natural photoperiods. Increases of milk production with 16 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
36
0
4

Year Published

1982
1982
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(51 citation statements)
references
References 20 publications
11
36
0
4
Order By: Relevance
“…Studies focused on understanding the endocrine effects of altering photoperiod have shown that circulating levels of prolactin increased when heifers and dairy cows were exposed to LDPP, melatonin decreased, but levels of growth hormone and glucocorticoids did not change Peters et al, 1981). The increased prolactin concentrations are believed to account in part for the increased mammary parenchymal weight in prepubertal and postpubertal heifers exposed to LDPP compared to heifers exposed to SDPP, and these effects carried through to production, as heifers exposed to LDPP produced more milk during their first lactation than SDPP (Petitclerc et al, 1985;Rius and Dahl, 2006).…”
Section: Circadian Rhythm and Mammary Function 397mentioning
confidence: 99%
See 2 more Smart Citations
“…Studies focused on understanding the endocrine effects of altering photoperiod have shown that circulating levels of prolactin increased when heifers and dairy cows were exposed to LDPP, melatonin decreased, but levels of growth hormone and glucocorticoids did not change Peters et al, 1981). The increased prolactin concentrations are believed to account in part for the increased mammary parenchymal weight in prepubertal and postpubertal heifers exposed to LDPP compared to heifers exposed to SDPP, and these effects carried through to production, as heifers exposed to LDPP produced more milk during their first lactation than SDPP (Petitclerc et al, 1985;Rius and Dahl, 2006).…”
Section: Circadian Rhythm and Mammary Function 397mentioning
confidence: 99%
“…A long-day photoperiod (LDPP), characterized as 16 h light (L) and 8 h dark (D), has been shown to hasten puberty and increase BW gain, feed efficiency, mammary parenchyma and prolactin concentration relative to animals exposed to short-day photoperiod (SDPP; 8L : 16D; Peters et al, 1981;Petitclerc et al, 1984;Zinn et al, 1986). LDPP also increases milk yield without increased consumption of feed , and exposure to SDPP during the dry period enhances subsequent lactation performance (Dahl, 2008).…”
Section: The Circadian Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Long day length has been shown to stimulate milk production during lactation but to impair milk fat in cattle (Peters et al, 1978 and1981;Stanisiewsky et al, 1985;Dahl et al, 2000 andPetitclerc, 2003), sheep (Bocquier et al, 1984(Bocquier et al, , 1990(Bocquier et al, and 1997 and goats . In contrast, short days, when applied during lactation, have a negative effect on milk production per se but increase the fat and protein contents of milk.…”
Section: Seasonality Of Reproductive Activity Is An Old Story First Smentioning
confidence: 99%
“…Chemineau et al 1996) Les variations saisonnières de la quantité et de la qualité (contenu en matières protéiques et grasses, comptage cellulaire) de la production laitière sont dues en partie à l'effet direct de la durée du jour sur la production et la composition du lait, et/ou sur le métabolisme général des femelles laitières. Les jours longs ont été démontrés comme ayant des effets stimulants pendant la lactation, mais ils limitent le contenu en matières grasses chez les bovins (Peters et al 1981 ;Stanisiewsky et al 1985 ;Dahl & Peticlerc, 2003), les ovins (Bocquier et al 1990(Bocquier et al , 1997 et les caprins (Delouis & Mirman, 1984). Au contraire, les jours courts, lorsqu'ils sont appliqués pendant la lactation, ont un effet négatif sur la production quantitative de lait, mais ils accroissent les contenus en protéines et en matière grasse.…”
Section: Utilisation De Traitements Photopériodiques Artificiels Pourunclassified